Use of differential absorbance to estimate concentrations of chlorinated disinfection by-product in drinking water: Critical review and research needs. Issue 2 (17th January 2018) - Beauchamp, Nicolas; Dorea, Caetano; Bouchard, Christian; Rodriguez, Manuel
ABSTRACT: Differential UV absorbance (ΔA) has been proposed as a method for estimating disinfection by-products (DBP) concentrations in drinking water at a lower cost and at higher frequencies than the sampling programs required by regulations. Various equations developed in laboratory settings between individual DBP concentrations and ΔA272 have been reported in the literature. Although the form of the DBP–ΔA relationships (linear or exponential) is shared by most published studies, the fitting parameters vary and must be calibrated for each site. This is usually explained by differences in the nature of the natural organic matter (NOM) reacting with free chlorine. This literature review suggests that future research should first focus on improving our understanding of the reaction between NOM moieties and chlorine, and its impact on UV absorbance spectra, and second on overcoming the challenges of applying ΔA for estimating DBPs in full-scale facilities.